BUILD OPERATE TRANSFER (BOT) AS BUSINESS ROLE MODEL FOR METERING SYSTEM AND DEVELOPMENT PROJECTS (STUDY CASES ON METERING SYSTEM PROJECT WHICH LOCATED AT PT. REXAUDIA SASADA SENTOSA) - Andrean, Dicky; Sugeng Santoso (Dinasti Publisher, 2020)
This research was carried out on Build Operate Transfer investment in Business cooperation model to metering system development project by examinated those criterias by technology preparedness level (TKT) evaluation method, Innovation preparedness level and political, social economic, technology, environment & legal aspects (PESTEL). This research was carried out to earned value from level of technological readiness level 8 and 9, Those innovation steady level 3 which involved several division like business development, engineering, accounting & finance, administration, human resources and health safety environtment officer. Gathered from all divisions and gave an score for TKT 8 assessment should be weight of more than 95% for accurate data criteria are ready, an assessment of TKT 9 has weight of more than 91% for technology criteria which tested in actual conditions, an assessment of Katsinov 3 has weighting of more than 94% for Manufacture Aspects, while assessment of PESTEL has a weight of more than 85% for Legal Aspect. Furthermore, these assessment results were brought up into focus group discussion by presented the Managing Director as expert judgment on final assessor of data validation, indicators, graphics and risk management planning before making decision about those Build Operate Transfer concept on investment business cooperation model to metering system of development project.